Four EFL teachers’ beliefs and practices of grammar teaching in Oman: an exploratory case study - Al-Qutaiti, Yaqoub Obaid; Sheikh Ahmad, Ismail (2018)
Teachers of English and other concerned educators dream to have students who never make grammatical mistakes. Therefore, in order to prepare their learners to be fluent and accurate speakers, readers, listeners, and writers, they have to make sure that students do not make grammatical mistakes frequently. EFL learners should see the difficulties, challenges, and rewards of using English accurately in addition, they ought to gain a better understanding of how language is structured and connected logically. More importantly, teachers and other educators should enhance the idea of how they can use correct English in real life as well as in their own classrooms. The main purpose of this qualitative study is to investigate four EFL teachers’ beliefs of grammar teaching, correcting students' grammatical mistakes and the challenges that they face when they teach grammar in the Omani context. Also, the study advocated some practical recommendations to EFL teachers, supervisors and curriculum designers ascribed to grammar teaching and learning. More significantly, by reading the four observed lessons in this research, the readers will obtain a myriad of empirical, stimulating ideas, meaningful comments and practical advice on how to teach grammar effectively. Therefore, these readers interested in language learning and teaching will be able to distinguish between the praised and discouraged grammar teaching practices; and augment their thoughts pertain to language grammar teaching in particular